Static compression test of materials - Lim, Christel Yi Hui (Nanyang Technological University, 2020)
Static compression test is a procedure where an escalating compressive load is applied to a certain material for a certain period until failure. It is used to determine the material’s ultimate yield strength, service life or other critical performance characteristics. By working closely with the American Society for Testing and Materials (ASTM) International Standards, specifically the Standard Test Methods of Compression Testing of Metallic Materials at Room Temperature (E9-09), specific testing procedures and methods are to be adhered to the experiments to ensure accuracy and precision of the overall study. For this Final Year Project (B169), static compression testing will be done on four medium sized as well as four long sized Aluminium Alloy 6061- T6511 rods using the Shimadzu AG-X plus 100kN machine. It is initiated by placing the specimen between two fixed compression plates of the Shimadzu testing machine, while an applied force gradually escalates up to 100kN. Strain gauges, attached onto the surface of the specimens, will be used to measure the strain values. And finally, the results of the experiment will be obtained for further analysis. The objective of this experiment is to identity and compare material properties that include stress, strain, yield strength, compressive strength and the Young’s Modulus of a specific material under a compressive load of 100kN. By obtaining data from the TrapeziumX Software as well as data logger, graphs of Force versus Displacement and the stress-strain curve will be plotted for suitable analysis of the materials properties. The main aim of this report is to evaluate and compare the overall results between the long and medium sized specimens, and at the same time, compare them with past reports to obtain optimal results that conforms to the material’s mechanical properties. And lastly, sophisticated recommendations will be provided for future researchers to achieve a greater standard of accuracy and precision.